Empowering and Disempowering Motivational Coaching Climate: A Scoping Review - Birr, Caroline; Hernández-Mendo, Antonio; Monteiro, Diogo; Rosado, Antonio (IOAP-MDPI, 2023)
The multidimensional model of empowering and disempowering coach climates has great relevance within the scope of intervention in the context of Sport Psychology. This scoping review of studies summarizes the scientific production of the empowering and disempowering motivational climates. The search comprised the Web of Science, Scopus, Psycinfo, and Pubmed databases for English, Portuguese, and Spanish articles published between 2013 and 2022. A total of 44 articles were found, of which 22 were included in the present study: 16 concerned cross-sectional studies, four were psychometrics validation studies, one involved a transversal cohort study, and one included a qualitative study. The questionnaire EDMCQ-C (Coach-created Empowering and Disempowering Motivational Questionnaire) is the most used and with the necessary psychometric qualities when it comes to assessing the empowering and disempowering motivational climates and their various impacts. We describe results concerning the measurement, antecedents, and effects of empowering and disempowering coach climates. Future research should invest in the study of empirical evidence that could be added to the existing nomological framework, considering antecedents, development, direct and indirect effects, moderating effects, aggregated effects, and qualitative studies.
Keywords: Psicología social; Coaching motivational style; Sport psychology; Scoping review